Hip fractures, preceding distal radius fractures and screening for osteoporosis: should we be screening earlier? A minimum 10-year retrospective cohort study at a single centre. Issue 1 (January 2016) - Daruwalla, Z.; Huq, S.; Wong, K.; Nee, P.; Leong, K.; Pillay, K.; Murphy, D.
Abstract Summary Both men and women who sustain a fracture of the distal forearm run an increased risk of sustaining a subsequent hip fracture. Our study implies that these patients may not necessarily constitute a group in which osteoporosis screening is warranted. Introduction People who sustain a distal radius fracture run an increased risk of sustaining a subsequent hip fracture. However, many institutions only screen for osteoporosis at the time of a hip fracture. We aimed to determine the true incidence of preceding distal radius fractures in an Asian population of patients with a hip fracture aged 60 years or older and whether screening for osteoporosis earlier would be beneficial. Methods We reviewed 22 parameters of 572 patients aged 60 years or older admitted after sustaining a hip fracture over a 3-year period. This included the occurrence or absence of a distal radius fracture in the 10 years preceding their hip fracture. Results Twenty-nine patients (5 %) had a fracture of the distal radius in the preceding decade. Univariate analyses suggested that hip fracture patients who had preceding distal radius fractures were older, female, have lower mean haemoglobin levels, and right-sided hip fractures. Of these factors, only age was found to have significant predictive value in a multivariate analysis. Conclusions A number of institutions have started to screen for osteoporosis when a patient presents with a fracture of the distal radius because these patients may have an increased risk of a subsequent hip fracture. Our study implies that this may not be warranted. Implementing such a screening service from both cost and resource utilization point of view must be studied prospectively and in greater detail considering earlier screening may only be beneficial to a very small percentage of patients.